Augmented Reality (AR) glasses for inspection of steel formwork system / Nurdayana Mohamad Suki and Wan Akmal Zahri Wan Zaharuddin - Mohamad Suki, Nurdayana; Wan Zaharuddin, Wan Akmal Zahri (2019)
Emergence of information technology (IT) in recent years has urge construction industry to adapt with the current Industrial Revolution (IR) 4.0. Aligned with technological advancement, Industrialized Building System (IBS) haslong commercialized in Malaysia that affects broad usage of Steel Formwork. System. Despite the advantages, problems continue to occur during the system's assembly and inspection since man-efficiency remain in the current practice. Presently, robotics system is common to assist human in operating jobs. Along with technology and robotic revolution, Augmented Reality (AR) appearsto be practical in most field as a potential reduction of errors. Desk study will be conducted in finding relevant research regarding AR technology as the solution to the identified problems. The expected findings of the study are to be able to identify the concurrent problems in the inspection of the system, determine AR concept and propose a solution to the problems. Derived from AR technology, a wearable instrument known by the name AR Glasses for Inspection of Steel Formwork System is proposed. The proposal shall contribute to problem rectification of inspection worksfor Steel Formwork System as well as providing possible implementation of advance technology in construction field.